(3GdfXQjI GdYGeI ddNHQI aj GdehGO GdLfGFjI (B: s (3aj VhA GJLGgGJ GdSjGSI GdLfGFjI GdMOjKI (B/ s - (3TQja fUQ CMeO s; (3YeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2010)
(3jOhQ ehVhY gPg GdOQGSI Mhd GdNHQI aj YdGbJgG HGdEKHGJ GdLfGFj hYdGbJgG HGdJWhQGJ GdYdejI GdMOjKI , hJJeKd ETcGdjJgG aj eOi edGFeI bhGYO GdNHQI dNUhUjI GdEKHGJ GdLfGFj , heOi caGjJgG ddJWhQGJ GdYdejI GdMOjKI , hJHOh CgejI GdOQGSI aj Cf GdNHQI JeKd Cbhi eXGgQ GdGYJeGO GdeJHGOd Hjf GdYde hGdbGfhf , hbO Je JbSje GdOQGSI dCQHYI CHhGH ; JfGhd GdHGH GdChd eGgjI GdNHQI , hJfGhd GdHGH GdKGfj ehVhY GdNHQI , hGfUH GdHGH GdKGdK Ydi TQhW UMI GdNHQI hBKGQgG HGdfSHI ddNHjQ, hJVef GdHGH GdCNjQ MLjI QCi GdNHQI hLRGA eNGdaI bhGYO GdNHQI, hbO GfJgJ GdOQGSI Edi YOe caGjI bhGYO GdNHQI GdNUhUjI GdEKHGJ GdLfGFj hGdJWhQGJ GdYdejI GdMOjKI, hef Ke abO ChUJ GdOQGSI HEYGOI JfXje HYV GdCMcGe , hef Pdc jejf GdNHQI EP jLH JMOjO UjZI dg hEdRGe GdNHjQ HCf jDOjg aj cd egeI , ceG JhUi GdOQGSI HVQhQI GdfU Ydi Cf jchf JbQjQ GdNHjQ ecJhHkG, ceG Cf GdNHQI GdQbejI JbJVi JfXjekG NGUkG , hjLH GdfU Ydi ELHGQ GdeJge Ydi GdNVhY dJMdjd GdHUeI GdhQGKjI EPG cGf GdJMbjb jbJVi Pdc(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2010.s
(3HHdjhLQGajG(B: (3UaMGJ (B513-545.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFj GdebGQfs; (3GdTQjYI GdESdGejIs; (3GdEKHGJ GdLfGFjs; (3GdHUeI GdhQGKjIs; (3GdWHjYI GdbGfhfjI ddNHQIs; (3Gdabg GdESdGej s; (3GdNHQIs; (3JbQjQ GdNHjQs; (3GdeSJTGQ Gdafj s; (3fXGe GdehGLgI aj GdNHQI s; (3GdNHQI hGdJQLeI s; (3GdNHQI hTgGOI GdTghOs; (3fXGe GdeQGbHIs; (3fXGe GdNHjQ GdhGMOs; (3fXGe GdKfGFjI hGdJYOOjI s; (3GdfXGe GdeNJdWs; (3GdOdjd GdQbej s; (3GdNHjQ GdQbej s; (3JbQjQ GdNHjQ s; (3Mbhb hGdJRGeGJ GdNHjQ s; (3UaI GdVHWjI GdbVGFjI ddNHjQ s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs